Feasibility Trial of Thumb Taping by Parents in Infants with Cerebral Palsy: Brief Report. (2nd January 2020) - Pearse, JE; Cadwgan, JE; Wisher, V; Jesmont, C; Mason-Burton, P; Barry, M; Jona James, J; Kelly, S; Basu, AP
ABSTRACT: Aim : To determine the feasibility and acceptability of parent-delivered elastic taping to the thumb and wrist in infants with cerebral palsy (CP). Design : Randomized cross-over feasibility trial. Participants : 20 infants (11 male; mean age 22 months) with CP. Intervention : Groups A and B received taping for 4 and 2 weeks, respectively. Outcomes : Primary : Recruitment and retention rates; adherence to protocol; Parent Satisfaction Questionnaire. Secondary : House Thumb score; Zancolli classification; Assisting Hand Assessment (AHA)/mini AHA. Exploratory : Duration of hand regard, thumb in palm, and open hand contact with toys during AHA/mini AHA. Results : Recruitment was feasible (95.2% uptake). Completion rates were 80% and 60% in Groups A and B. Questionnaire feedback was generally positive. Some parents reported increased awareness of the taped hand. Objective improvements were rare though one participant showed consistent improvement in thumb position. Conclusion : Taping proved feasible and acceptable; individual case benefit suggests further research is required. Trial registration : ISRCTN41918400.